Effects of Hormone Therapy on Body Composition and Metabolic Parameters in Postmenopausal Women with Obesity: A Pharmacological Approach - Sánchez-Paredes, José Luis; Talavera Inofuente, Juan Carlos; Valladares-Vega, Macarena (Journal of Neonatal Surgery, 2025)
Menopause is associated with hormonal changes that can influence body composition and metabolic parameters, increasing the risk of obesity and cardiovascular disease. This study analyzes the impact of hormone therapy (HT) on body composition and metabolic parameters of postmenopausal women with obesity. A review was conducted of recent studies that evaluated the efficacy of HT in reducing fat mass, visceral fat, and improving lipid and glycemic profiles. The results suggest that HT, especially that administered orally, may have positive effects on body fat redistribution and improvement of metabolic parameters, although more research is required to establish definitive clinical recommendations